Travels in the great desert of Sahara in the years of 1845 & 1846 : containing a narrative of personal adventures during a tour of nine months through the desert amongst the Touaricks and other tribes of Saharan people : including a description of the oases and cities of Ghat, Ghadames, and Mourzuk /: containing a narrative of personal adventures during a tour of nine months through the desert amongst the Touaricks and other tribes of Saharan people : including a description of the oases and cities of Ghat, Ghadames, and Mourzuk. ([2013?]) - Richardson, James, 1806-1851
No abstract available